Konsep Ilmu Menurut Syed Muhammad Naquib Al-Attas (Analisis buku Islam Dan Filsafat Sains) - Lailah Alfi Alfi (Universitas Darussalam Gontor, 2018)
Concept of Science in Islam is a very important thing to know al-Ḥaqq. Al-Qur'an and Ḥadith contains repeatedly the word “science” and its derivatives, which occupy the second after the word “tawheed”. Al-Attas had said in his work entitled